Kontribusi Retribusi Pantai Yen Beba Terhadap Pendapatan Asli Daerah Kabupaten Manokwari - Sudarwadi, Hustianto; Baransano, Siti R.N; Werimon, Simson (Fakultas Ekonomi dan Bisnis Universitas Papua, 2025)
ABSTRACT This study aims to analyze the effectiveness and contribution of tourism object retribution at Yen Beba Pasir Putih Beach to the Regional Original Revenue (PAD) of Manokwari Regency during the period 2022–2024. The research employs a qualitative descriptive approach, with data collection techniques including interviews, observations, and documentation conducted at the Department of Tourism, Creative Economy and Culture, the Regional Revenue Agency, and the management of the tourism object. The results indicate that the effectiveness level of tourism object retribution increased annually, reaching 7% in 2022, 40% in 2023, and 120% in 2024, which reflects an improvement in retribution management performance. However, the contribution of tourism object retribution to PAD remains very small, accounting for only 0.07% in 2022, 0.52% in 2023, and 2.16% in 2024. Therefore, it has not yet made a significant contribution to the Regional Original Revenue of Manokwari Regency. The increase in effectiveness was influenced by the growth in the number of visitors, from 23,259 people in 2022 to 38,958 people in 2024, as well as improvements in tourism facilities. Nevertheless, to strengthen the tourism sector as a more substantial source of PAD, it is necessary to enhance regulatory frameworks, improve infrastructure and facilities, intensify promotion efforts, and encourage active community participation. Keywords: Retribution, Effectiveness, Contribution, Regional Original Revenue. ABSTRAK Penelitian ini bertujuan untuk menganalisis efektivitas dan kontribusi retribusi obyek wisata Pantai Yen Beba Pasir Putih terhadap Pendapatan Asli Daerah (PAD) Kabupaten Manokwari pada periode 2022-2024. Metode yang digunakan adalah pendekatan deskriptif kualitatif, dengan Teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi pada Dinas Pariwisata Ekonomi Kreatif dan Kebudayaan, Badan Pendapatan Daerah, serta pengelola obyek wisata. Hasil penelitian menunjukkan bahwa tingkat efektivitas retribusi obyek wisata mengalami peningkatan dari tahun ke tahun, yaitu 7% pada 2022, 40% pada 2023, 120% pada 2024, yang berarti kinerja pengelolaan retribusi semakin baik. Namun demikian, kontribusi retribusi terhadap PAD masih tergolong sangat kecil, yakni hanya 0,07% pada 2022, 0,52% pada 2023, dan 2,16% pada 2024, sehingga belum mampu memberikan sumbangan signifikan bagi PAD Kabupaten Manokwari. Peningkatan efektivitas ini dipengaruhi oleh meningkatnya jumlah dari 23.259 orang pada 2022 menjadi 38.958 orang pada 2024 serta adanya perbaikan fasilitas wisata. Meskipun demikian, untuk menjadikan sektor pariwisata sebagai sumber PAD yang lebih besar, diperlukan penguatan regulasi, peningkatan sarana prasarana, promosi serta partisipasi aktif masyarakat. Kata Kunci: Retribusi, Efektivitas, Kontribusi, Pendapatan Asli Daerah.